2011
DOI: 10.1007/s12011-011-9045-6
|View full text |Cite|
|
Sign up to set email alerts
|

The Toxicological Effects in Brain of Mice Following Exposure to Cerium Chloride

Abstract: Cerium (Ce) compounds are now widely applied in medicine, agriculture, animal breeding, and daily life; however, the effects of Ce on human body, especially on the central nervous system, are still unclear. In order to investigate whether Ce exposure cause neurotoxicological effects, ICR mice were exposed to CeCl(3) through intragastric administration at 0, 2, 10, and 20 mg/kg body weight doses everyday for 60 days. The behaviors of spatial recognition memory, brain histopathology, the brain elements and neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…To investigate whether Ce exposure causes neurotoxicological effects, ICR mice were exposed to CeCl 3 through intragastric administration at 0, 2, 10, and 20 mg/kg for 60 days. The results indicated that CeCl 3 exposure could impair the learning ability, which is attributed to the disturbance of the homeostasis of trace elements, enzymes, and neurotransmitter systems in the mouse brain [58]. The study investigated the signal pathway of hippocampal apoptosis induced by intragastric administration of CeCl 3 for 60 days.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate whether Ce exposure causes neurotoxicological effects, ICR mice were exposed to CeCl 3 through intragastric administration at 0, 2, 10, and 20 mg/kg for 60 days. The results indicated that CeCl 3 exposure could impair the learning ability, which is attributed to the disturbance of the homeostasis of trace elements, enzymes, and neurotransmitter systems in the mouse brain [58]. The study investigated the signal pathway of hippocampal apoptosis induced by intragastric administration of CeCl 3 for 60 days.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have suggested that the reduction in learning and memory in rats or mice caused by La 3+ and Ce 3+ were related to significant increases in acetylcholine (Ach), glutamic acid (Glu), and nitric oxide (NO), and marked decreases in neurotransmitters such as norepinephrine (NE), 5-hydroxy tryptophan and its metabolite 5-hydroxy indole acetic acid, as well as dopamine and its metabolite 3, 4-dihydroxyphenylacetic acid [18], [22]. In addition, Ce 3+ exposure resulted in a significant reduction in Ca 2+ concentration in mouse brain [18].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Ce 3+ exposure resulted in a significant reduction in Ca 2+ concentration in mouse brain [18]. Ln 3+ -induced neurotransmitter and Ca 2+ changes were thought to be related to alterations in gene expressions in the brain [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute exposure to high-dose of toxic metals has been indicated to be capable of inhibiting NO x levels in vivo and in vitro [22, 49, 50]. Recently, accumulated evidence has reported that the chronic exposure to toxic insults induces significant alteration of Na + /K + -ATPase activities in brain accompanied with the whole blood and/or brain NO x changes [12, 51, 52] and increased or decreased the whole blood NO x levels, which closely correlates with the exposure to low dose of mercurial compounds-induced neurotoxicity, has been revealed [13, 21, 34]. Here, our results demonstrated that Na + /K + -ATPase activities in the cerebral cortex, cerebellar cortex, and brainstem of offspring were significantly increased after the administration of a low dose of cinnabar for 7 consecutive weeks (the F1-C-Cin group), which were related to the increase of NO x levels in the whole blood.…”
Section: Discussionmentioning
confidence: 99%